The natural renewable building material-bamboo. A comparison between Germany and Indonesia. - Haves, Felix Bernhard (Journal of A Sustainable Global South, 2019)
It is foreseeable worldwide that in the future the topic of sustainability will have to be given greater importance. The same applies to the building industry. Bamboo is a natural, very fast growing raw material with very good properties which have great advantages in many areas. It doesn't grow all over the world, but it already has a lobby in non countries of origin. Now the question arises whether bamboo can become more important in the future as a building material in non-countries of origin due to sustainability problems.  First of all the work deals with the climatic conditions that bamboo needs to grow and why it can't grow all over the world. Subsequently, bamboo as a raw material is discussed and it is worked out whether it has the right properties for an alternative and what could make it such a good alternative material. It is examined whether he can supplement or even replace other materials in countries of origin. Properties are confronted and compared. My results show that bamboo, due to its properties and applications, has the potential to be a complement and/or an alternative to other building materials. However, there are some small factors that speak against it. Further my results have shown that fundamentally much more thought has to be given to sustainable building. Bamboo can become a big factor of sustainability in the building industry in the future, but it is not enough to rest on it and the topic must be given a more important meaning. Index Terms — Bamboo,Future,Non-Originating Countries,Sustainability.